Design of Purchase and Sales Information Systems at Bima Citra Stores - Jasmir, Jasmir; Agustina, Agustina; Meisak, Despita (International Conference on Business Management and Accounting, 2023)
Bima Citra shop is a place of business in Tanjung Jabung Barat Regency, which is located on Jl.Imam Bonjol, Kuala Tungkal. Bima Citra shop is engaged in the sale of office stationery, school stationery, and so on whose data collection process is still using the manual method, namely still using handwritten notes for sales. With this system there are frequent recording and calculation errors that make the owners not know for sure whether they are experiencing profits or losses every day, besides that there are obstacles between physical stock data that are not recorded so that there is a difference in stock in the warehouse. This problem causes losses so that an information system is needed that provides convenience in providing information. This causes the owner to be overwhelmed in handling incoming and outgoing stock of goods because it is not recorded and does not recap so it is not known for sure how much stock is still available. Therefore, this study aims to design a purchasing and sales information system using the PHP programming language, MySQL DBMS as a database, waterfall system development method and system modeling in the form of use case diagrams, activity diagrams, and class diagrams. The result of this research is a system that helps manage business processes, such as processing data on purchases, sales, stock and is able to streamline time in reporting reports.